7x-3x=6x+14

Simple and best practice solution for 7x-3x=6x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-3x=6x+14 equation:


Simplifying
7x + -3x = 6x + 14

Combine like terms: 7x + -3x = 4x
4x = 6x + 14

Reorder the terms:
4x = 14 + 6x

Solving
4x = 14 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
4x + -6x = 14 + 6x + -6x

Combine like terms: 4x + -6x = -2x
-2x = 14 + 6x + -6x

Combine like terms: 6x + -6x = 0
-2x = 14 + 0
-2x = 14

Divide each side by '-2'.
x = -7

Simplifying
x = -7

See similar equations:

| 6x-(5-1)=2 | | 0.25n+60= | | 81t^3-4t=0 | | 7x-4=-2x+9x-5 | | 2(x-4)+9=5x-3(-x+1) | | (6x+8)(3x+38)= | | -172=-20(-4b) | | 15x^2+80+80x=0 | | 9g+4g=52 | | 14+3n=3(n-4) | | 2x^2+3x-4=8 | | 12p-15p=6 | | (6x+12)(2x)= | | 6x-1=2x-3 | | 2x^2+6=14 | | 2-2=11y-2y | | -4m-3=2+1m | | 6p-18p=24 | | 6(-27-8)=7(-27-3) | | 4r-15=8r+1 | | p=7x-2y | | (9x-2)=(4x+13) | | (3x-50)(2x-5)= | | -12(3-2x)=44(-5x+7) | | -19x=551 | | 5m-2(m+2)=(-2m+15) | | -24=4z | | (9x+2)=(4x+13) | | 5(x-9)=4(x+9) | | 4x+20=6x | | 5x+x=4 | | p^3-pq^2-p^2q+q^3=0 |

Equations solver categories